Approach of sensor network backup based on smart and cooperative network - Di MIAO; Bin HUANG; Jie LI (网络与信息安全学报)
In order to solve the problem of routing reliability in sensor nodes,a kind of sensor network backup mechanism based on smart and cooperative network was studied.The Leach algorithm was used to carry out the backup of the cluster sensor,and the method of the sensor backup and starting the backup sensor was presented.The tests on Mini-Net show that sensor backup mechanism can effectively solve the sensor failure network outages,with the advantage of fast handoff and low delay.